3D tumor detection in automated breast ultrasound using deep convolutional neural network. Issue 11 (6th October 2020) - Li, Yanfeng; Wu, Wen; Chen, Houjin; Cheng, Lin; Wang, Shu
Abstract : Purpose: Automated breast ultrasound (ABUS) has drawn attention in breast disease detection and diagnosis applications. Reviewing hundreds of slices produced by ABUS is time‐consuming. In this paper, a tumor detection method for ABUS image based on convolutional neural network is proposed. Methods: First, integrating multitask learning with YOLOv3, an improved YOLOv3 detection network is designed to detect tumor candidate in two‐dimensional (2D) slices. Two‐dimensional detection separately treats each slice, leading to larger differences of position and score for tumor candidate in adjacent slices. Due to the influence of artifact, noise, and mammary tissues, 2D detection may include many false positive regions. To alleviate these problems, a rescoring processing algorithm is first designed. Then three‐dimensional volume forming and FP reduction scheme are built. Results: This method was tested on 340 volumes (124 patients, 181 tumors) with fivefold cross validation. It achieved sensitivities of 90%, 85%, 80%, 75%, and 70% at 7.42, 3.31, 1.62, 1.23, and 0.88 false positives per volume. Conclusion: Compared with existing ABUS tumor detection methods, our method gets a promising result.